Effects of surface micro-structures on capacitances of the dielectric layer in triboelectric nanogenerator: A numerical simulation study. (January 2021) - Xi, Yinhu; Zhang, Fan; Shi, Yijun
Abstract: Triboelectric nanogenerator (TENG) provides a promising approach for energy harvesting and sensing. Micro-structures are often employed at dielectric layer for improving efficiency, but the effects on the electric output performance of TENG are not well understood. In this work, we conduct a numerical simulation study based on the planar capacitor analytical method to study the electric output performance for contact-separation (CS) TENG. Different from previous work, which only investigates the effects on the real contact area, this work also studies the effects of the surface micro-structures on the capacitance and the consequent effects on the electronic output performance. The separation to contact open circuit (OC) output voltage is focused on, which is widely employed for sensor applications. The effects of the capacitance variations on OC output voltages under different elastic modulus and micro-structure geometrical parameters are investigated. The results indicate that the capacitance variations can even lead up to more than 100% deviation of the OC output voltages, which confirms that the effect of the capacitance variations is also an important factor. More importantly, it is found that some existing experimental data cannot be explained/simulated by models without consideration of the capacitance variations, and it is more correct to use the ratio of real contact area to capacitance variations to predict the open circuit output voltage of TENG instead of only using contact area when the micro-structure size is larger than 10 µm. Graphical Abstract: ga1 Highlights: A numerical model for calculating electric outputs of CS TENG with surface micro-structures has been proposed. The separation to contact operation is focused. Capacitance variations causing by the surface micro-structure deformation are considering. Ratios of real contact area to capacitance variation are more correct to predict the OC output voltage.